Teacher Strategies to Improve Students’ Learning Motivation in History Class: A Descriptive Qualitative Study in SMP Negeri 19 Palu - Almaidah Almaidah; Iskandar Iskandar; Minarni Nongtji; Lukman Lukman (Journal of Educational Sciences, 2026)
The research investigates how teachers at SMP Negeri 19 Palu work to boost student motivation in history classes. The researchers used descriptive qualitative research methods to study how teachers implement their methods and assess their effects on student motivation. The study involved a history teacher and seventh-grade students as its participants. The researchers collected data through observation, interviews, questionnaires, and documentation. The researchers used qualitative analysis methods to analyze data by conducting data reduction, data presentation, and conclusion drawing processes. The findings demonstrate that teachers use different methods to create a learning environment which helps students increase their motivation from learning materials that teachers connect to their real-world experiences. The methods used by teachers lead to higher levels of student excitement and classroom involvement which drives their interest in studying history. The research establishes that effective teaching methods which require teachers to develop innovative strategies play a vital role in enhancing student motivation and advancing the educational system. Teachers should develop new teaching methods which focus on student needs to maintain and boost student motivation for learning activities.